Simultaneous Estimation of Torsemide and Spironolactone and forced Degradation Studies in Bulk and Combined Dosage form by RP-HPLC - S.RAJALAKSHMI,; L.KIRAN KUMAR,; V.KRISHNA PRIYANKA,; Y.MANOHAR, (International Journal of Pharma and Bio Sciences, 2018)
Torsemide is a loop diuretic and Spironolactone is a high ceiling diuretic, which belong to diuretics class of drugs. Diuretics increases the rate of urine flow .A simple RP-HPLC method was developed for the simultaneous estimation of Torsemide and Spironolactone in bulk and tablet dosage form according to International Council of Harmanisation guidelines. High Pressure Liquid Chromatography instrument used was an auto-sampler, software used was Empower. The mobile phase was 80% ACN with 0.1% OPA buffer at a flow rate of 1ml/min, wave length was 235 nm (iso-bestic point) detected by UV detector. Empower software was used and elution was isocratic mode. The oritical plate count was >2000 and RSD was less than 1. Injection volume was 20 µL RT was 3.1 & 3.9, linearity concentrations were found to be 50-250 µg/ml and 125-625 µg/ml respectively. Correlation coefficient was r2=0.999. Recoveries were 99.7% & 99.4%. LOD/LOQ was also done for both the drugs. LOD was found to be 3.3 and LOQ was found to be 10. They were subjected to acid, alkali, peroxide and oxidative treatments, photo degradation etc., The method validation was performed with respect to robustness, specificity, linearity, precision and accuracy were checked.